Determinants of Intention to Pay ZISWAF Trought BSI Mobile in Indonesia - Sarmilah, Sarmilah; Afdawaiza, Afdawaiza (UIN Raden Mas Said Surakarta, 2024)
Customer intention in paying ZISWAF through BSI mobile is important to investigate because ZISWAF are important instruments to reduce the level of poverty in Indonesia. The aim of this study is to determine the factors influencing customers' interest in making ZISWAF payments through BSI mobile. This research employs the Technology Acceptance Model (TAM) theory, incorporating two additional internal variables, namely trust and security. A quantitative approach is used to examine the relationship between dependent and independent variables, utilizing primary data obtained directly from Indonesian Sharia Bank customers through the distribution of 220 questionnaires. Subsequently, the data is processed using the Partial Least Square Structural Equation Model (PLS-SEM) approach. The results indicate that perceived usefulness and security variables have a positive impact on the interest in paying ZISWAF, perceived ease of use and trust variables do not affect the interest in making zakat and waqf payments through BSI mobile in Indonesia.